Nigerian university libraries in consortia: past, present and future challenges (2005)
The paper surveys library consortia and efforts among Nigerian Universities at sustaining them. It traces history of the efforts of Universities (State and Federal) and in recent times Private ones, and notes the strengths, weaknesses and strategies for proposed improvement. It is discovered that past library consortia have not been properly sustained. The Jew still in existence have problems such as funding, inability to network properly, inadequate or non-existent Information Technology (IT) infrastructure, transportation and sometimes administrative bureaucracy. Library consortia in recent times are seen to be moving more into I.T formats. Prospects in this area are explored. Recommendations are made for strengthening of existing consortia and building up of new ones where applicable, to put University Education back on the high pedestal where it belongs.